Strategic Plan 2020-2025 - Prendergast, Patrick J.; Barkhoff, Jürgen (Trinity College Dublin - University of Dublin, 2020)
Taken from the Provost's introduction to the Strategic Plan "This Strategic Plan will shape the future of this university to benefit Irish society and the wider world. The plan’s title, ‘Community and Connection’, reflects our conviction that, in an increasingly interdependent world, we need to work together more intensely and in new ways to address the formidable challenges facing us."
Keywords: Strategic Plan